Some properties of compatible action graph - Shahoodh, M. K.; Mohd Sham, Mohamad; Yuhani, Yusof; Sahimel Azwal, Sulaiman (Penerbit UMP, 2021)
In this paper, the compatible action graph for the finite cyclic groups of p-power order has been considered. The purpose of this study is to introduce some properties of the compatible action graph for finite p-groups.